(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
The presentation of undergraduate courses and action dissemination promoted by the university to society is relevant, as it makes knowledge accessible to the population and supports the decision-making process of those who wish to get into Higher Education. In this study, we aim to present the lived experiences in the twelfth edition of the extension project "Feira do Vestibular" (Admittance Exam Fair) from the Bragança Campus, whose main objective was to present the undergraduate courses offered by the Bragança Campus at the Federal University of Pará, and to resolve the main doubts of candidates for the vacancies offered in the selection processes. The actions were planned and developed through videoconferences, in compliance with the protocol of social distancing due to the Covid-19 pandemic. Talks and seminars between students and professors of each course were the methodologies. The programming was recorded and broadcast through social networks: Facebook, Instagram, and YouTube including the “Educadora FM” radio. The actions were fundamental for information socialization, reflection on the education’s importance for personal and professional development, and the university’s role and relevance to society.